If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(1-x)-2(x-2)=2-4(x-4)
We simplify the equation to the form, which is simple to understand
6(1-x)-2(x-2)=2-4(x-4)
Reorder the terms in parentheses
+(+6-6x)-2*(x-2)=2-4*(x-4)
Remove unnecessary parentheses
+6-6x-2+*(+x-2+)=+2-4+*(+x-4+)
Reorder the terms in parentheses
+6-6x+(-2x+4)=2-4*(x-4)
Remove unnecessary parentheses
+6-6x-2x+4=+2-4+*(+x-4+)
Reorder the terms in parentheses
+6-6x-2x+4=2+(-4x+16)
Remove unnecessary parentheses
+6-6x-2x+4=+2-4x+16
We move all terms containing x to the left and all other terms to the right.
-6x-2x+4x=+2+16-6-4
We simplify left and right side of the equation.
-4x=+8
We divide both sides of the equation by -4 to get x.
x=-2
| x^2+11=350 | | (1/5)(45-X) | | (2x+5)/(7x+22) | | 12x+15y=1000 | | 9-21=y-2+16 | | 75=n+4n | | 87-116=-4(-4y)-9(2y)+y | | N^3=-35-12n | | X^2+6x-r=-9 | | 24=2g-6 | | -1/7+7=5/7 | | (3x^2+2x-1)-(x^2-4x-7)= | | (3x^2+7x+9)-(7x-8)= | | (-4x^2+10x+15)+(3x^2-2x-4)= | | (3x^2-x+2)(16-x^2)= | | 2y-(3+7y)=11-3y | | (7x^2-14x+25)+(3x^2+3x-4)= | | -90=-10(-3b) | | x^3=5x-4x^2 | | (3x^2-4x+2)+(x^2+3x-4)= | | 4e+9= | | -(2-4(-3+1)+2)/9(-1-2) | | 0=8x-x^3 | | 102-6x=21x+18 | | (2x^2+3x-1)+(4-6x)= | | 50=-5(5p) | | (1450-105/1450)100=x | | (1450-105/1450)100=0 | | 2=31/4+n | | x^3-17x^2+90x-144=0 | | 0=(16x^2)+400 | | (1450-y/1450)100=.928 |